A new Euchalcia Hübner, [1821] from Qinghai, China (Lepidoptera: Noctuidae - Saldaitis, Aidas; Volynkin, Anton V.; Benedek, Balázs (Zootaxa, 2019)
The Palaearctic genus Euchalcia Hübner, [1821] is a member of the subfamily Plusiinae, family Noctuidae. Currently it includes 53 valid species and 6 subspecies (Ronkay et al. 2008; Volynkin et al. 2014). The E. gerda species-group includes E. gerda (Püngeler, 1907), E. caelestissima Hreblay & Ronkay, 1998, E. serraticornis Dufay, 1965 and E. bea Hreblay & Plante, 1998 (Ronkay et al. 2008). During examination of more than 80 specimens identified as E. gerda collected in several localities in the Chinese province of Qinghai and deposited in the collections of Péter Gyulai (Miskolc, Hungary), Alessandro Floriani (Milan, Italy) and World Insect Gallery (Joniškis, Lithuania), we found two strange looking specimens having more elongated forewings with a well-developed pinkish suffusion. Despite the wide range of an individual variability being characteristic for species of the E. gerda species-group, these two specimens showed morphological differences from E. gerda as well as from other related species, and thus proved to be new for science. The description of this new species is given below.